The inspired aquarium : ideas and instructions for living with aquariums - Senske, Jeff.; Senske, Mike. (Gloucester, Mass. : Quarry Books, 2006)
"The Inspired Aquarium" is a key tool to use while searching for ideas to help inspire your own home-aquarium design. This complete handbook acts as both an inspirational and factual guide. It shows you the most compatible choices in aquatic creatures, plants, lighting, and more for your chosen setup.
Includes bibliographical references (p. 170-172) and index.
Keywords: Aquariums